Analysis of physical phenomena associated with asteroid deect by kinetic impact - Chagas, Bruno [UNESP]; De A. Prado, Antonio F.B. [UNESP]; Winter, Othon Cabo [UNESP] (My University, 2021)
We have as objective for the present work, to study the use of a kinetic impact technique as a way to deect asteroids that may present some risk of collision with the Earth at a certain moment, or even the interest in approaching the asteroids with the intention of studying or mining them, something that is being discussed a lot now a days. Within the work to be developed here, we intend to evaluate in more detail the possibility of deecting the orbit of asteroid 101955 Bennu, making variations in its velocity (v) in different orbital periods and measuring the variation in its minimum distances with the planet Earth. We will also present the inuence of the planets of the solar system dubbing the application of the technique of orbital deviation of small bodies in the final results.
Keywords: asteroids; astrodynimics.; Bennu; deect; kinetic impact